2022
DOI: 10.1021/acsami.2c08986
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Foam Stabilized by a CO2-Responsive Surfactant and Similarly Charged Cellulose Nanofibers for Reversibly Plugging in Porous Media

Abstract: CO2 foams are of great importance in oil recovery but challenging in some aspects like long-term stabilization and time-separated conflict. In this work, a stability-enhanced switchable foam was fabricated using bis-(2-hydroxyethoxy) olefine amine (BOA) and trace amounts (0.05 wt %) of cationic-modified cellulose nanofibers (CCNFs). The CCNF was developed using sequentially functionalized CNF with diamine groups, which were essential to promote the aqueous dispersibility and a key for strengthening the stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…As expressed in the section of the mechanical strength of PVA−CNF hydrogel in acid−base and salt-involved conditions in the Supporting Information (Figure S10), it can be acquired that PVA−CNF hydrogel can maintain its network structure without serious damage in the range of pH = 2−13 and the saline environments, which indicated that PVA−CNF hydrogel has the excellent stability and adaptability to the harsh water environment of the reservoir. It is well known that the application of hydrogel for water shutoff in oilfields is as follows: the polymer-based sol of relatively low viscosity (<10 mPa•s) was injected in the high-permeable zone of the reservoir and it in situ polymerizes to form hydrogel with time or temperature in the micro-channels, 32 thus acting as a physical barrier to hinder water production or to reduce the permeability of high-permeable zone.…”
Section: Prospective Applications In Oilfieldsmentioning
confidence: 99%
“…As expressed in the section of the mechanical strength of PVA−CNF hydrogel in acid−base and salt-involved conditions in the Supporting Information (Figure S10), it can be acquired that PVA−CNF hydrogel can maintain its network structure without serious damage in the range of pH = 2−13 and the saline environments, which indicated that PVA−CNF hydrogel has the excellent stability and adaptability to the harsh water environment of the reservoir. It is well known that the application of hydrogel for water shutoff in oilfields is as follows: the polymer-based sol of relatively low viscosity (<10 mPa•s) was injected in the high-permeable zone of the reservoir and it in situ polymerizes to form hydrogel with time or temperature in the micro-channels, 32 thus acting as a physical barrier to hinder water production or to reduce the permeability of high-permeable zone.…”
Section: Prospective Applications In Oilfieldsmentioning
confidence: 99%